British HIV Association guidelines for prescribing antiretroviral therapy in pregnancy (1998). Issue 2 (1st April 1999) - Taylor, G P; Lyall, E G; Mercey, D; Smith, R; Chester, T; Newell, M L; Tudor-Williams, G
Abstract : The aim of antiretroviral therapy in pregnancy is to deliver a healthy uninfected child to a healthy mother, without prejudicing the future treatment opportunities of the mother. The use of zidovudine monotherapy rapidly became standard practice once it had been shown to reduce by 67% mother to child transmission in women with CD4+ lymphocyte counts above 200 x 10(6)/l. High rates of transmission are seen when maternal disease is advanced (high viral load, low CD4+ lymphocyte counts) despite zidovudine. In these women highly active antiretroviral therapy gives the best prospect for prolonged health and it is anticipated that reducing plasma viral load below the limits of detection will further reduce transmission rates. However, safety data for antiretroviral therapy in pregnancy are limited and each additional treatment exposes a significant proportion of uninfected infants to potential long term hazards. Where maternal therapy is not indicated and the sole objective of treatment is to reduce mother to child transmission, recent data suggest that short course zidovudine (especially in conjunction with prelabour caesarean section) is a reasonable option. This may minimise the emergence of viruses with reduced sensitivity to zidovudine and preserve maternal options for later therapy.